Final answer:
To prove whether the expression (p ∨ ¬q) ∧ (q ∨ ¬r) ∧ (r ∨ ¬p) is true or false, we need to consider two cases: when p, q, and r are all true, and when they are all false.
Step-by-step explanation:
To prove that the expression (p ∨ ¬q) ∧ (q ∨ ¬r) ∧ (r ∨ ¬p) is true when p, q, and r have the same truth value and false otherwise, we need to consider two cases:
If p, q, and r are all true.
In this case, the expression evaluates to (true ∨ ¬true) ∧ (true ∨ ¬true) ∧ (true ∨ ¬true).
Simplifying further, we get true ∧ true ∧ true, which is true.
If p, q, and r are all false.
In this case, the expression evaluates to (false ∨ ¬false) ∧ (false ∨ ¬false) ∧ (false ∨ ¬false).
Simplifying further, we get false ∧ false ∧ false, which is false.
Therefore, the expression (p ∨ ¬q) ∧ (q ∨ ¬r) ∧ (r ∨ ¬p) is true when p, q, and r have the same truth value and false otherwise.